Long-range PCR sequencing as a novel approach in genetic—analysis of MYH3: A preliminary result - Wan Rohani, Wan Taib; Wan Pauzi, Wan Ibrahim; Sathiya, Maran (2015)
Background and objective: Genetic diagnosis of large genes are usually complicated by large transcript size, complexity of the gene region and the high level of gene variations. Long-range PCR is a flexible, fast, efficient and cost-effective choice for sequencing large candidate genomic regions, especially when combined with next-generation sequencing (NGS) platforms. This article aims to develop and optimise novel mutation screening assay for MYH3 gene which is 40 kb in size by directly sequencing four LR-PCR products using Illumina MiSeq sequencing platform. Methods: Genomic DNA was isolated from 1 mL of peripheral blood was extracted using GeneAll DNA extraction kit (GeneAll, Korea), following the manufacturer’s protocol. Four sets of primers that span the entire gene were synthesised. MaxTaq DNA Polymerase (Vivantis) was used to amplify each amplicons with cycling conditions; 94 °C for 2 min, 94 °C 12, annealing temperature for 30, 68 °C for 10 mins, 68 °C for 7 min for a total of 35 cycles. The amplified amplicons were pooled together and library was prepared using Nextera XT DNA Sample Preparation Kit (Illumina Inc., CA, USA). Pooled library was generated by mixing all libraries equally for high-throughput sequencing on MiSeq™ Benchtop Sequencer (Illumina Inc., CA, USA). The sequence was aligned to the hg19 assembly of the genome with BWA enrichment analysis tool (Illumina Inc., CA, USA) and variants were called using Variant Studio (Illumina Inc., CA, USA). Only variants with at least 6-fold read coverage and a phred scale SNP ≥30 were included for further analysis. Results: The four 10 kb amplicons were successfully amplified with annealing temperatures; 63.1, 62.4, 64.7 and 64.7 ºC respectively, employing standard PCR cycling method within a short period of time. Targeted sequencing using Illumina MiSeq paired-end sequence resulted in 11,947,785 reads (98.05%) of which 99.8% could be aligned with the human genome. This provided 99.8% coverage of the sequence at a minimum sequencing depth of 6×. With this method, a total of 2,280 known variants and 848 unknown variants were detected, which will be subjected to further downstream analysis. Conclusions: Current method enables amplification of the entire gene with four reactions, each generating product sizes of 10 kb circumventing the need for specific PCR amplification of individual exons. LR-PCR allows direct sequencing and screening methods for detecting genetic variations, achieving high sensitivity and improved intronic coverage with a faster turnaround time and lower costs, and providing a reliable tool for complex genetic analyses.